2021
DOI: 10.1037/neu0000770
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of effects of cognitive reserve on performance in probable Alzheimer’s disease and in subjective cognitive decline.

Abstract: OBJECTIVE:Cognitive reserve (CR) is a term used to describe the adaptability of cognitive processes to brain changes. It helps to explain the differential cognitive adaptation to daily functioning in aging individuals and in individuals with brain pathology, with a higher CR associated with a delay in the manifestation of cognitive symptoms. CR can be estimated using different proxies, such as education, life experience, premorbid IQ, and vocabulary size.Despite the complexity of CR, little research to date ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…Their results showed that patients with AD showed increased EEG synchrony in the theta band in frontal and occipital regions compared to patients with SCD. These differences could be explained by the degradation or lower cognitive reserve in patients with AD (Montemurro et al, 2021 ).…”
Section: Pathological Agingmentioning
confidence: 99%
“…Their results showed that patients with AD showed increased EEG synchrony in the theta band in frontal and occipital regions compared to patients with SCD. These differences could be explained by the degradation or lower cognitive reserve in patients with AD (Montemurro et al, 2021 ).…”
Section: Pathological Agingmentioning
confidence: 99%
“…Based on a previous investigation (Montemurro et al, 2021b), in which it has been shown a relevant and selective interaction between Age and a composite life experience CR proxy (but not for Education) in individuals without agerelated disease, an additional analysis was made to further explore such interaction. In line with the variables included in the study, we included in the additional analysis the variable Sex.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The primary advantage of GAMs over linear regressions is their ability to efficiently treat, through smooth functions, complex non-linear relations between predictors and the dependent variable. GAMs allowed investigating the interaction between continuous variables through tensor surfaces, (something that cannot be handled by GLM); for a recent application of GAM with neuropsychological tests see Yu et al (2020); Montemurro et al (2021b). The reported p values of the GAM analyses are corrected through the Bonferroni method according to the total number of tests performed.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations